Physical Conditions of Fast Glacier Flow: 3. Seasonally‐Evolving Ice Deformation on Store Glacier, West Greenland. Issue 1 (30th January 2019) - Young, T. J.; Christoffersen, P.; Doyle, S. H.; Nicholls, K. W.; Stewart, C. L.; Hubbard, B.; Hubbard, A.; Lok, L. B.; Brennan, P. V.; Benn, D. I.; Luckman, A.; Bougamont, M.
Abstract : Temporal variations in ice sheet flow directly impact the internal structure within ice sheets through englacial deformation. Large‐scale changes in the vertical stratigraphy within ice sheets have been previously conducted on centennial to millennial timescales; however, intra‐annual changes in the morphology of internal layers have yet to be explored. Over a period of 2 years, we use autonomous phase‐sensitive radio‐echo sounding to track the daily displacement of internal layers on Store Glacier, West Greenland, to millimeter accuracy. At a site located ∼30 km from the calving terminus, where the ice is ∼600 m thick and flows at ∼700 m/a, we measure distinct seasonal variations in vertical velocities and vertical strain rates over a 2‐year period. Prior to the melt season (March–June), we observe increasingly nonlinear englacial deformation with negative vertical strain rates (i.e., strain thinning) in the upper half of the ice column of approximately −0.03 a −1, whereas the ice below thickens under vertical strain reaching up to +0.16 a −1 . Early in the melt season (June–July), vertical thinning gradually ceases as the glacier increasingly thickens. During late summer to midwinter (August–February), vertical thickening occurs linearly throughout the entire ice column, with strain rates averaging 0.016 a −1 . We show that these complex variations are unrelated to topographic setting and localized basal slip and hypothesize that this seasonality is driven by far‐field perturbations in the glacier's force balance, in this case generated by variations in basal hydrology near the glacier's terminus and propagated tens of kilometers upstream through transient basal lubrication longitudinal coupling. Plain Language Summary: Ice sheets deform when subject to changes in its flow regime. Such deformation impacts the shape of and distance between internal layers within ice sheets. Through the development of a high‐precision stationary radar, we can measure the vertical compression or expansion between internal layers through time. We used this methodology at an inland location on Store Glacier in western Greenland to obtain a 2‐year‐long record of ice deformation. The records show that this location on Store Glacier stretches and compresses throughout the year, sometimes with both occurring at the same time on top of each other. Using satellite imagery, we discover that the deformation regime at our study site is linked to seasonal changes in the flow farther down the glacier nearer to the ocean. If this section slows down, then the ice will thicken farther up the glacier; similarly, faster flow at the terminus will stretch and thin the ice behind it. Key Points: Autonomous phase‐sensitive radar can be used to track the fine‐scale motion of glacier internal layers Vertical velocity profiles of internal layers evolve seasonally in a region of fast flow Changes in the local strain field are driven by downstream far‐field longitudinal stress coupling